Intercriteria Analysis as Tool for Acoustic Monitoring of Forest for Early Detection Fires; Advances in Intelligent Systems and Computing; Vol. 1081 : Uncertainty and Imprecision in Decision Making and Decision Support: New Challenges, Solutions and Perspectives - Sonkin M. A. Mikhail Arkadjevich; Khamukhin A. A. Aleksandr Anatolievich; Pogrebnoy A. V. Aleksandr Vladimirovich; Marinov P. Pencho; Atanassova V. Vasa; Roeva O. Olimpia; Atanassov K. Krasimir; Alexandrov A. Alexandr (Advances in Intelligent Systems and Computing book series, 2021)
Title screen